GAMBARAN PENGETAHUAN DAN SIKAP WISATAWAN MANCANEGARA TENTANG KESELAMATAN BERKENDARA DI DESA KUTA - Telaumbanua, Desniati; Eva Yanti, Ni Luh Putu; Rahajeng, Indah Mei (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p02, 2025)
Traffic accidents are a global problem and one of the causes of death among foreign tourists. Safety riding is an important aspect to avoid danger, risk, and loss. This study aims to determine the description of the knowledge and attitudes of foreign tourists about safety riding in the village of Kuta. This research used quantitative methods, where the type of this research is descriptive using cross sectional research design. The sample in this study amounted to 97 foreign tourists and was selected using the consecutive sampling technique. Data were collected using an online questionnaire. The results of the study show that respondent’s knowledge about safety riding is the good category 33%, the sufficient category 25.8%, and the low category 41.2%. The result on respondent’s riding attitude is the good category 42.3 %, the sufficient category 34%, and the less category 23.7%. Based on these results can be concluded that the knowledge of foreign tourists in low category and attitude of foreign tourists in good category. It is recommended to the owner of a vehicle rental service to ensure the understanding of foreign tourists about traffic regulations in Bali by conducting socializing the importance of safety riding and imposing conditions that must be owned by foreign tourists such as license for riding a motorbike ownership before motorbike rentals.